Exploring possible ontogenetic trajectories in tyrannosaurids using tracks from the Wapiti Formation (upper Campanian) of Alberta, Canada. Issue 6 (10th December 2020) - Enriquez, Nathan J.; Campione, Nicolás E.; Brougham, Tom; Fanti, Federico; White, Matt A.; Sissons, Robin L.; Sullivan, Corwin; Vavrek, Matthew J.; Bell, Phil R.
ABSTRACT: Fossil tracks should theoretically capture differences in pedal anatomy between growth stages of the same taxon, particularly those related to the soft tissue of the foot, providing a more realistic view of pedal ontogeny than skeletal material alone. However, recognizing these ontogenetic trajectories is complicated by the influence of preservation and kinematics on track morphology, as well as the inherent difficulty of referring different tracks to a single taxon. Here, we explore differences in track morphology from a collection of tracks attributed to tyrannosaurids from Unit 4 of the Wapiti Formation (upper Campanian) in western Canada. Along with morphology, close geographic and stratigraphic associations suggest that the tracks pertain to similar tyrannosaurid trackmakers. A geometric morphometric analysis of the track outlines reveals size-dependent increase in relative track robusticity, driven primarily by an increase in 'heel' breadth and surface area. This relationship is lost when the dataset is expanded to include tyrannosaurid tracks globally, which we attribute to increased stratigraphic and taxonomic 'noise' within the global dataset that masks the tightly constrained patterns obtained from the Wapiti Formation tracks. Although there is some substrate and kinematic influence on certain aspects of track morphology, we hypothesize that the observed size-dependent relationship reflects genuine expansion in the breadth of the heel soft tissues and probably their overall surface area associated with growth. Increased pedal robusticity likely assisted with weight bearing and locomotor stability as body mass increased over ontogeny, supporting previous hypotheses that some tyrannosaurids underwent a growth-related reduction in relative agility and/or cursorial performance.